Karakteristik Kimia Bekasam Ikan Nila (Kajian Penambahan Lactobacillus Acidophilus dengan Variasi Waktu Pengukusan) - Gama Dian Nugroho; Anjas Setiawan; Rinto Rinto; Herpandi Herpandi (Jurnal FishtecH, 2023)
This research aims to determine the effect of the steaming time periods and the addition of L.acidophilus on the chemical of Tilapia Bekasam. The study used factorial randomized block design (RCBD) with two treatment factors namely steaming time peroids (A) consisting of 3 levels of steaming treatment (0, 5, 10 minutes) and The addition of L. acidophilus (B) consisting of 2 levels of treatment (addition and without L. acidophilus) with three repetitions. The observed chemical parameters included moisture, protein, fat, ash, and carbohydrate content. The results of the chemical analysis showed the addition of L. acidophilus and the steaming time period has a significant effect on the value of moisture content (57.19 - 60.73%), protein content (18.68- 21.99%), fat content (5.07 -9.34%) while the addition of L. acidophilus had no significant effect on ash content (6.93-9.87%) and carbohydrate content (2.51-5.92%).